The role of the Glorious Qur’an in achieving societal peace in Salah al-Din Governorate - Jinan Shaker Ali (Islamic Sciences Journal, 2025)
ABSTRACT This research aims to study the impact of electronic communication networks on promoting social peace from an Islamic perspective. This is achieved by analyzing the jurisprudential foundations that regulate public discourse through these media, while utilizing a practical model represented by Salah al-Din Governorate. The importance of this study stems from the growing social and legal challenges resulting from the misuse of these networks, and the resulting societal disintegration, the spread of discord, and the deepening of sectarian discourse.The study's results showed that social media can positively contribute to promoting social peace if jurisprudential and ethical guidelines are observed in its use, particularly in light of the presence of awareness-raising models in of Salah al-Din Governorate that have helped reduce hate speech and fostered values of tolerance and constructive communication.